Pandemic planning - Dietz, J. Eric; Black, David R. (CRC Press, 2012)
"Offering research and evidence-based guidelines for strategic plan development, this book draws on the lessons learned over three years of pandemic preparedness exercises. Collaborating with national leaders and community stakeholders, the contributing authors examine preparedness across a variety of institutional levels and consider the issues and concerns that may arise throughout the process. The book details the threat of pandemic illness and the need and actions required for efficient and effective preparation, prevention, response, and recovery to a pandemic threat at all levels -- community, state, and regional"--